Over a million students use our free study notes to help them with their homework
Equal out the x terms so 12x+8y=32 and 9y+12x=33Then subtract the first equation from the secondThis gives y=1Put this value into one of the equations so 12x+8=32Solve the equation giving x as 2.
The first step is to expand the brackets by multiplication. This can be done using the 'bird method'. This results in 4m – 8 = 5mt + 3tNow to collect all 'm' like terms of the equation on the LHS. This gi...
Factorise the equation: (3x+3)(x+1) = 0. Anything multiplied by 0 is equal to 0 therefore (x+1)=0 and (3x+3) = 0. Solve for x: if x+1 =0 you need to subtract 1 from x to work out what x is (do the opposi...
We differentiate each term individually with respect to x. the way we differentiate powers of x is: x^n goes to nx^(n-1). So x^2 would become 2x, 2x would be just 2 as x^0 is 1 and a constant would just d...
←
441
442
443
444
445
→
Internet Safety
Payment Security
Cyber
Essentials